The fragility of consciousness : faith, reason, and the human good - Lawrence, Frederick G.; Rosenberg, Randall S.; Vander Schel, Kevin (2017)
"The Fragility of Consciousness is the first published collection of his essays and contains several of his best known writings as well as unpublished work. The essays in this volume exhibit a long interdisciplinary engagement with the relationship between faith and reason in the context of the crisis of culture that has marked twentieth- and twenty-first century thought and practice. Frederick G. Lawrence, with his profound and generous commitment to the intellectual life of the church, has produced a body of work that engages with Heidegger, Gadamer, Habermas, Ricoeur, Strauss, Voegelin, and Benedict XVI among others. These essays also explore various themes such as the role of religion in a secular age, political theology, economics, neo-Thomism, Christology, and much more. In an age marked by social, cultural, political, and ecclesial fragmentation, Lawrence models a more generous way--one that prioritizes friendship, conversation, and understanding above all else."--
Martin Heidegger and the hermeneutic revolution -- Hans-Georg Gadamer and the hermeneutic revolution -- Gadamer and Lonergan on Augustine's Verbum Cordis - the heart of postmodern hermeneutics -- A Jewish and Christian approach to the problematic of Jerusalem and Athens: Leo Strauss and Bernard Lonergan -- Voegelin and Gadamer: continental philosophers inspired by Plato and Aristotle -- "Transcendence from Within": Benedict XVI and Jürgen Habermas on the dialogue between secular reason and religious faith -- The fragility of consciousness: Lonergan and the postmodern concern for the other -- The recovery of theology in a political mode: the example of Ernest L. Fortin, AA -- The economic good of order and culture in relation to solidarity, subsidiarity, and responsibility -- The human good and Christian conversion -- Grace and friendship: postmodern political theology and God as conversational -- Growing in faith as the eyes of being-in-love with God.
Includes bibliographical references and index.
Keywords: Hermeneutics -- Religious aspects -- Christianity; Theology; Faith and reason; Christianity and culture; Christian ethics; Christian ethics; Christianity and culture; Faith and reason; Hermeneutics -- Religious aspects -- Christianity; Theology